2006
DOI: 10.4074/s0003503306002016
|View full text |Cite
|
Sign up to set email alerts
|

L’inférence haptique d’une localisation spatiale chez les adultes et les enfants : étude de l’effet du trajet et du délai dans une tâche de « complètement de triangle »

Abstract: Cette étude cherche à savoir si l'inférence d'une localisation d'un point dans la modalité haptique par des adultes et enfants (travaillant sous occlusion visuelle momentanée) est influencée par la nature du trajet effectué pour l'atteindre et le délai entre la phase d'exploration et la réponse. Pour répondre à ces questions, nous avons proposé le paradigme de complètement de triangle : les participants, les yeux bandés , doivent explorer avec leur index les deux premières branches d'un triangle isocèle, conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…They observed that a 10-s delay significantly improved performance. They suggest that a shift from the egocentric towards the allocentric reference frame during the delay period would lead to different spatial processing (for discussion, see also Faineteau et al 2005 ; Gentaz and Gaunet 2006 ).…”
Section: General Discussion and Perspectivesmentioning
confidence: 99%
“…They observed that a 10-s delay significantly improved performance. They suggest that a shift from the egocentric towards the allocentric reference frame during the delay period would lead to different spatial processing (for discussion, see also Faineteau et al 2005 ; Gentaz and Gaunet 2006 ).…”
Section: General Discussion and Perspectivesmentioning
confidence: 99%
“…So, in line with the results of previous studies, which found that two hands are better than one (Craig, 1985;Heller, Hasselbring, Wilson, Shanley, & Yoneyama, 2004), we would expect that one-fingertip perceptions would be less powerful than the perceptions coming from 10 fingers of the two hands to build a cognitive map that should be able to integrate information in both the ego and allocentric frames of reference. Millar (1994) and Gentaz and Gaunet (2006) proposed that the use of a haptic modality to encode small-scale space is based mainly on the memorization of the movement of kinesthetic information. Hatwell, Streri, and Gentaz (2003) argued that the quality of mental spatial images is dependent on the depth, exposure, and detail of the encoding.…”
Section: Discussionmentioning
confidence: 99%
“…Ce mode de codage serait à l'oeuvre indépendamment de l'expérience visuelle des sujets et seulement lorsque le système épaule-main des adultes serait largement engagé au cours de l'exploration. Un mode de codage similaire serait aussi à l'oeuvre pour les tâches où les sujets voyants (adultes et enfants) ou aveugles doivent inférer la localisation spatiale d'un point à partir d'une exploration manuelle (Gentaz et Gaunet, 2006 ;Gaunet & Gentaz, sous presse).…”
Section: Effet De L'interaction Des Deux Indices -Distance Et Localisunclassified